Bridging the Gap: Teacher Self-Efficacy and Inclusive Education Implementation in Cambodia - Phonn Sophak (JF Publisher, 2026)
This study examined teachers' disability-inclusive education background and its relationship with self-efficacy in instruction, collaboration, and managing behaviour within the Cambodian context. Employing a mixed methods design, quantitative data were collected from 533 teachers (403 general education, 130 special education) across five provinces using an 18-item self-efficacy questionnaire, whilst qualitative secondary data underwent SWOT analysis. Statistical analyses including Confirmatory Factor Analysis, Structural Equation Modelling, and independent samples t-tests were conducted using SPSS AMOS Version 29. Results revealed significant positive relationships between teachers' self-efficacy dimensions and both disability-inclusive education background and implementation outcomes. Special education teachers demonstrated significantly higher self-efficacy in instruction (M = 3.10 vs 2.54, p < .001) and collaboration (M = 3.02 vs 2.59, p < .001) compared to general education teachers. However, 47 per cent of teachers reported no inclusive education training, whilst 35 per cent had no experience teaching children with disabilities. SWOT analysis identified supportive policies and increased awareness as strengths, but revealed critical weaknesses including inadequate training and negative staff attitudes. These findings underscore urgent need for systematic professional development interventions to enhance teacher self-efficacy and advance Cambodia's inclusive education implementation aligned with the Inclusive Education Action Plan 2024-2028.